Johannes W. Flume, Marktaustausch - Schmolke, Klaus Ulrich (2020)
In der ERCL, 2020, Band 16, Heft 4, S. 557-561 rezensiere ich die Habilitationsschrift "Marktaustausch" von Johannes W. Flume (Tübingen, Mohr Siebeck, Jus Privatum 235, 2019).<br